Numerical Investigation of Plastic Deformation in Two-turn Equal Channel Angular Extrusion - Mitsak, A.; Aour, B.; Khelil, F. (Engineering, Technology & Applied Science Research, 2014)
There has been a number of investigations in recent years reporting on the structure and properties of materials deformed to super plastic deformation (SPD). During SPD new textures can be formed and abnormal characteristics are displayed, attracting a growing research interest.¶ Equal channel angular extrusion (ECAE) is a method often used to obtain large plastic strains. However, according to experimental results, there is a large tensile stress in the sample during deformation, which may lead in some cases, to cracking in metallic alloys and large curvature in polymeric materials. In order to overcome these drawbacks, the ECAE process can be conducted at high temperatures. But this contributes significantly to a decreased level of plastic deformation induced in the sample. Hence, a tool with multi-pass seems to be a very appropriate solution. In this paper, a new geometry die composed of two elbows has been simulated by finite element method aiming to provide an insight into the mechanisms of deformation and to determine the optimum geometry of the tool. The numerical results show that the length and the section of the second channel play a significant role on the homogeneity of the plastic strain distribution. It has been found that good homogeneity was obtained when the second channel has the same section as that of the entrance and the exit channels and with a length equal to three times of its width.